Biallelic mutations in KATNAL2 cause male infertility due to oligo‐astheno‐teratozoospermia. Issue 4 (11th June 2021) - Wei, Xiaoli; Liu, Wensheng; Zhu, Xingshen; Li, Youzhu; Zhang, Xiaoya; Chen, Jing; Isachenko, Vladimir; Sha, Yanwei; Lu, Zhongxian
Abstract: Oligo‐astheno‐teratozoospermia (OAT) is a common cause of male infertility, and most of idiopathic OAT patients are thought to be caused by genetic defects. Here, we recruited 38 primary infertile patients with the OAT phenotype and 40 adult men with proven fertility for genetic analysis and identified biallelic mutations of KATNAL2 by whole‐exome sequencing in two cases. F013/II:1, from a consanguineous family, carried the KATNAL2 c.328C > T:p.Arg110X homozygous mutations. The other carried c.55A > G: p.Lys19Glu and c.169C > T: p Arg57Trp biallelic mutations. None of the KATNAL2 variants were found in the 40 adult men with proven fertility. The spermatozoa from patients with KATNAL2 biallelic mutations exhibited conspicuous defects in maturation, head morphology, and the structure of mitochondrial sheaths and flagella. KATNAL2 was mainly expressed in the pericentriolar material and mitochondrial sheath of the spermatozoa from control subjects, but it was undetectable in the spermatozoa from the patients. Furthermore, Katnal2 null male mice were infertile and displayed an OAT phenotype. Our results proved that the biallelic mutations in KATNAL2 cause male infertility and OAT in humans for the first time, to our knowledge, which could enrich the genetic defect spectrum of OAT and be beneficial for its accurate genetic screening and clinical diagnosis. Abstract :